Opioids for the management of dyspnea in patients with heart failure: a systematic review of the literature - León-Delgado, Marta; Rodríguez-Campos, Luisa; Bastidas-Goyes, Alirio; Herazo-Cubillos, Andrés; Martin-Arsanios, Daniel; Muñoz-Ortíz, Juliana; Cifuentes-Serrano, Annie; García-Ávila, Paloma; Beltrán-Caro, Mateo (Colombian Journal of Anesthesiology, 2019)
Introduction: Heart failure is a chronic, progressive, prevalent disease, with a high impact on health systems and on the quality of life of patients and families. Dyspnea is a common symptom and management with opioids has been proposed. Objective: To conduct a systematic review of the literature pertaining to the use of opioids for the management of dyspnea in patients with stable chronic heart failure, functional class New York Heart Association (NYHA) II, III, or IV. Materials and methods: A systematic review was conducted in the MEDLINE, Embase, Cochrane, OVID, LILACS, and PROSPERO databases of articles published in 5 languages between January 1, 1995 and July 31, 2018. Studies describing the administration of any type of opioid for the management of dyspnea in patients with stable chronic heart failure NYHA II, III, or IV were included. Results: Four clinical trials were obtained for the final analysis with a total number of 70 patients, describing opioid administration for the management of dyspnea in patients with stable chronic heart failure, NYHA II, III, or IV. Conclusion: In adult patients with compensated chronic heart failure under optimum treatment, there is low-quality evidence that shows benefit with the use of opioids for the management of dyspnea. For a stronger recommendation, controlled, randomized studies with a larger number of subjects are required.